PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD Student Teori Achievement Division (STAD) PADA BIDANG STUDI IPA DI SD NGALIYAN 07 SEMARANG - Sri Sulistyorini (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
The goal of this research are as follows: I) To improve student's achievement by applying cooperative teaching, 2) To know the student's cooperative skill, 3) To analyze the teacher's skill in manag• ing cooperative teaching, 4) To get some information about student's response to cooperative teaching. The technique of collecting data in this research are testing sheet instrument to reveal a student's achievement. Observation sheet to analyze teacher's skill in teaching activity and student's cooperative skill, and questionnaire to reveal student's response to the teaching. The results obtained from to applying of cooperative model are: Can improve the student's achievement, there is a skilled teacher in managing teaching activity, the student active in teaching activity and the student feel enjoy with cooperative learning. The conclusion of this research is the cooperative teaching model of STAD type can be applied in elementary school because it can improve student's achievement, so that, they become active and enthusiastic